1976
DOI: 10.1111/j.1471-4159.1976.tb04471.x
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Analysis of Sodium Dependent Glutamic Acid Transport in Peripheral Nerve

Abstract: —The kinetics of sodium dependent glutamic acid transport have been studied in desheathed frog sciatic nerve. Initial velocities have been measured as a function of both glulamic acid and sodium concentration. Lineweaver–Burk plots are constructed from these data, and the kinetic constants describing uptake are estimated. Vmax is unaffected by sodium concentration, which implies that translocation is not directly affected by sodium. K1 is sodium dependent, which implies that sodium affects the affinity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The role of sodium in choline high-affinity uptake was investigated by replacing Na+ with other monovalent cations. The one-half maximal uptake rate achieved using sodium concentrations between 40 and 6 0 d , was quite similar to values reported by Haga and Noda (1973) for choline accumulation, by Wheeler (1976) for glutamate uptake, and by Martin and Smith (1972) for GABA transport of rat synaptosomes. The observed sodium effect is consistent with 116 BREER the concept that choline uptake is partially driven by the sodium electrochemical gradient (Kuhar and Murrin, 1978;Vaca and Pilar, 1979).…”
Section: Discussionsupporting
confidence: 84%
“…The role of sodium in choline high-affinity uptake was investigated by replacing Na+ with other monovalent cations. The one-half maximal uptake rate achieved using sodium concentrations between 40 and 6 0 d , was quite similar to values reported by Haga and Noda (1973) for choline accumulation, by Wheeler (1976) for glutamate uptake, and by Martin and Smith (1972) for GABA transport of rat synaptosomes. The observed sodium effect is consistent with 116 BREER the concept that choline uptake is partially driven by the sodium electrochemical gradient (Kuhar and Murrin, 1978;Vaca and Pilar, 1979).…”
Section: Discussionsupporting
confidence: 84%
“…Most studies, where there are sufficient data, indicate that influx is more or less a function of the first power of [Na +] (Eddy, Mulcahy & Thomson, 1967;Inui & Christensen, 1966;Wheeler & Christensen, 1967b;Thomas & Christensen, 1971;Evans, 1973Evans, , 1975Sprott et al, 1975;Wheeler, 1976). Some, like the present one, indicate that it is largely or entirely a function of [Na+] 2 (Vidaver, 1964a;Baker & Potashner, 1971;Peterson & Raghupathy, 1972Wheeler & Hollingsworth, 1978).…”
Section: The Effect Of Na + Ions On Ku Vm~x and Ktmentioning
confidence: 51%
“…There are four important studies of the Na +-dependent component of L-glutamate influx into nerve preparations. Dependence on the first power of [Na +] was found by Wheeler (1976) for bullfrog (Rana catesbeiana) sciatic nerve, and by Evans for peripheral nerves from the walking legs from crabs (C. maenas) (1973) and for cockroach (P. americana) abdominal nerve cord (1975). Wheeler found that Kt was dependent on [Na +] while I/max was unaffected and furthermore showed that his observations were consistent with the reaction of inactive carrier with Na + to form a 1 : 1 complex which transported glutamate.…”
Section: The Effect Of Na + Ions On Ku Vm~x and Ktmentioning
confidence: 97%
See 1 more Smart Citation
“…It is unlikely that sodium ions also enhance the translation rate of either unloaded or hypotaurine-loaded carriers across cell membranes, because the maximal velocities of transport remained about the same. Likewise in synaptosomes and peripheral nerve it was the affinity of the carrier for glutamic acid that was directly affected by sodium rather than the translocation rate of glutamic acid (Bennett et al, 1973;Wheeler, 1976;Wheeler and Hollingsworth, 1978). In contrast, the omission of sodium ions has also been reported to affect the K , more than the V in synaptosornal GABA transport (Martin, 1973).…”
Section: Discussionmentioning
confidence: 99%